Transforming Teacher Performance: Optimizing Learning Through Information and Communication Technology - Endra Priawasana; Pipit Rika Wijaya (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2024)
This study aims to explore the effect of information and communication technology (ICT) usage on teacher performance at Madrasah Aliyah in Jember Regency. The background of this research is the low quality of teachers in Indonesia, as indicated by the 2015 Teacher Competency Test (UKG) results, with a national average score of only 44.5, far below the standard of 75. A quantitative method with a descriptive approach was used to collect data from 40 teachers as samples, using a questionnaire that had been tested for validity and reliability. Data analysis employed descriptive statistical analysis, classical assumption tests, and simple linear regression. The research results show that ICT usage has a significant impact on teacher performance, with a regression coefficient value of 0.809, meaning that every 1% increase in ICT usage improves teacher performance by 80.9%. The T-count value of 4.904 is greater than the T-table value of 2.035, with a significance level of 0.000, indicating a significant influence. Additionally, the R-Square value of 0.422 indicates that 42.2% of the variability in teacher performance can be explained by ICT usage, while the remaining 57.8% is influenced by other factors. The study also identifies various digital tools and platforms used by teachers, such as Moodle, Google Classroom, Kahoot!, and Quizlet, which contribute to improved teaching performance. However, the study also notes challenges in ICT implementation, including accessibility, technological skills, and curriculum integration. These findings provide a comprehensive view of how ICT can be effectively utilized in education and the challenges that need to be addressed to maximize its benefits. This study has practical and theoretical implications, including recommendations for the use of technology in teaching and the addition of literature on ICT utilization in education